2022
DOI: 10.2340/17453674.2022.1517
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E infused highly cross-linked cemented cups in total hip arthroplasty show good wear pattern and stabilize satisfactorily: a randomized, controlled RSA trial with 5-year follow-up

Abstract: Background and purpose — Vitamin E infused highly cross-linked polyethylene (VEPE) was introduced in order to enhance oxidative resistance in highly cross-linked polyethylene cups in total hip arthroplasty (THA). We have, with a follow-up of 5 years, evaluated wear characteristics of 2 identically designed cemented cups with the only difference being the material, VEPE or ultra-high molecular weight polyethylene (UHMWPE). Furthermore, we report cup migration and clinical outcome. Patients and methods — 48 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Their patients were older (mean 70) than in our trial but underwent their surgery by the posterior approach, which might influence their physical functioning. In the study of Bergvinsson et al the HOOS scores seem similar to our results [ 32 ]. Lyman et al reported comparable results: slightly higher scores at Symptoms and QoL subscales, lower score on the ADL subscale and equal for Pain [ 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Their patients were older (mean 70) than in our trial but underwent their surgery by the posterior approach, which might influence their physical functioning. In the study of Bergvinsson et al the HOOS scores seem similar to our results [ 32 ]. Lyman et al reported comparable results: slightly higher scores at Symptoms and QoL subscales, lower score on the ADL subscale and equal for Pain [ 33 ].…”
Section: Discussionsupporting
confidence: 91%